THE IMPACT OF WORKFORCE DIVERSITY ON FIRM PRODUCTIVITY AT SERVICE OFFICE OF STATE PROPERTY AND AUCTION (KPKNL) MANADO - Rumerung, Chrisdy; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Workforce diversity is a mix of people within a workforce who are considered to be, in some way different from those in the prevailing constituency. Organizations have recognized the importance of embracing policies and practicing to diversity their workforces because it helps enhance competitiveness, build talent, expand organizational capabilities, and enhance access to markets like diverse customer bases. The benefits of diversity are achieved by acknowledging the strengths diversity can bring to organization. Service office of state property and auction (KPKNL) Manado is one of firm in Manado as one of base of workforce diversity that come not just from Manado but also from outside Manado. KPKNL Manado became representative for firm that haves foundation of workforce diversity. The objective of this research is to analyze factors workforce diversity on firm productivity especially in KPKNL Manado. Research method that had been used for this research is associated with multiple linear regression analysis technique. The population in this research is all employees at KPKNL Manado with sample as many as 36 respondents. This shows that workforce diversity (age diversity, educational diversity and gender diversity) has impact toward firm productivity and age diversity is the most significant factor that affects to firm Productivity at KPKNL Manado.Â  Keywords: workforce diversity, firm Productivity